Two new taxa of Achnanthidium and Encyonema (Bacillariophyceae) from the Yom River, Thailand, with special reference to the areolae occlusions implying ontogenetic relationship - Ekkachai Yana (2018)
© 2015 Japanese Society of Phycology. We discovered two new taxa of Achnanthidium and Encyonema occurring with high abundance in the upstream of the Yom River, which is one of four major rivers in Northern Thailand. Achnanthidium pseudoconspicuum var. yomensis var. nov. closely resembles Achnanthidium pseudoconspicuum var. pseudoconspicuum in scanning electron microscopy (SEM), but has clearly different valve morphometry under the light microscopy (LM). Achnanthidium pseudoconspicuum var. yomensis is also similar to A.japonicum in valve morphology under LM, but differs to this species based on SEM observation. Encyonema yuwadeeanum sp. nov. shows similarities to Encyonema leei and Encyonema subkukenanum, but differs in valve shape and/or polar fissure shape. We discuss the possible valve ontogenetic relationship between Achnanthidium and Cymbellales based on the detailed areolae structures of these two new taxa.